2021
DOI: 10.1108/tqm-06-2021-0188
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of kaizen culture and its effect on operational performance: perspective of manufacturing companies in Malaysia

Abstract: PurposeThe purpose of this research is to examine the effect of kaizen culture on innovation and operational performance of electrical and electronic manufacturing companies in Malaysia. A research framework, with underpinning theories of dynamic capabilities and socio-technical systems, was conceptualized to investigate the interplay of these relationships.Design/methodology/approachData were collected from 123 manufacturing companies using an online survey and analyzed with IBM SPSS Statistics version 24.0 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 58 publications
(170 reference statements)
0
4
0
Order By: Relevance
“…The kaizens increased the production from 45 products per hour to 51 products per hour. Mui et al (2021) also observed that for firms to improve their operational performance, a kaizen culture is essential. The productivity improvement achieved the high customer demand of 388 assemblies per day.…”
Section: Improvement Of Productivity and Line Efficiencymentioning
confidence: 99%
“…The kaizens increased the production from 45 products per hour to 51 products per hour. Mui et al (2021) also observed that for firms to improve their operational performance, a kaizen culture is essential. The productivity improvement achieved the high customer demand of 388 assemblies per day.…”
Section: Improvement Of Productivity and Line Efficiencymentioning
confidence: 99%
“…, 2023). Although some organisations increase efficiency, effectiveness and competitive advantage through innovation in their processes (Siew Mui et al. , 2022), many pieces of research revealed that huge investments in innovation and technology impact efficiency and effectiveness only for a while (Alosani and Al-Dhaafri, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, successful Kaizen implementation necessitates an appropriate culture (Miller et al. , 2014; Siew Mui et al. , 2021; Kong and Muthuveloo, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, successful Kaizen implementation necessitates an appropriate culture (Miller et al, 2014;Siew Mui et al, 2021;Kong and Muthuveloo, 2022). Previous experiences have proven that long-term changes do not occur in the absence of an appropriate culture (Siew Mui et al, 2021;Kong and Muthuveloo, 2022), particularly a culture based on innovation (Kong and Muthuveloo, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation